ENHANCING STUNDENT’S SCIENTIFIC ATTITUDE USING INQUIRY LEARNING MODELS FOR SCIENCE SUBJECT CLASSROOM IN 5TH GRADE STUDENT OF SD NEGERI PRAWIT I NO.69 YEAR OF ACADEMIC 2017/2018 - Ermi Widyaningsih; Jenny Indrastoeti Siti Poerwanti; Chumdari Chumdari (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
The aim of this research is to enhance the student's scientific attitude using inquiry learning method in the science classroom. This study used classroom action research method done in three cycles. Every cycle provide planning, acting, observing and reflecting. The method of collecting data used observation, interview and documentation. Technique triangulation, source triangulation and informant review used to check the data validity. Data analysis technique used in this study was interactive model. The conclusion of this research showed the use of inquiry learning succesfully enhance student's scientific attitude for science classroom in 5th grade of SD Negeri Prawit 1 No. 69 Surakarta year of academic 2017/2018.